(untitled) (Revue El-Wahat pour les Recherches et les Etudes, 2025)
This study aims to understand the role that digital public relations play in attracting external audiences to the Algerian Telecommunications Institution in Biskra. Digital public relations have introduced new methods that rely on the internet and its technologies and platforms to influence, persuade, and attract the external audience to the services provided by the organization in its field of work. The goal is to enhance the interactive capacity between the organization and its external audience. The study used a survey methodology, applying a questionnaire to gather information from the participants, who are employees of the Algerian Telecommunications Institution in Tolga Biskra, we have reached the following results: Digital public relations management contributes to attracting the external audience to the Algerian Telecommunications Institution in Biskra through: Relying on tools and methods that help attract the external audience, such as digital advertising, the institution’s official websites, the Internet, and social media platforms—particularly Facebook. The quality of services and messages provided by the digital public relations department to the external audience is characterized by credibility and security in transmitting and disseminating information, as well as the speed and quality of the services offered, in addition to the improvement in the external audience’s interaction with the institution. Keywords: Public Relations, Digital Public Relations, External Audiences.